Mental Health and Psychological Impact of Cyberbullying on Adolescents: A Bibliometric Study - Sutipyo Ru'iya; Muhammad Farid; Sujono Riyadi; Hafid Ulinnuha (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The rapid growth of social media and internet use has increased the risk of cyberbullying, especially among adolescents. This issue became more prominent during the COVID-19 pandemic, as digital activity surged, creating greater opportunities for online harassment. The psychological impact of cyberbullying on students has become a global concern. This study aims to analyze global publication trends related to the impact of cyberbullying on adolescent mental health over the last decade. Methods: A bibliometric analysis was conducted using data from the Scopus database, covering publications from 2015 to 2025. A total of 636 relevant documents were identified, focusing on psychology, public health, medical science, and social sciences. The analysis was performed using VOSviewer and R Studio, with key terms such as cyberbullying, mental health, and psychological impact. Results: The results indicate a steady rise in publications on cyberbullying and adolescent mental health, with notable growth in recent years. The United States was the most productive country, with strong international collaboration patterns. Key research topics included cyberbullying, mental health, adolescents, and emotional outcomes such as anxiety and depression. The dominance of certain journals and keywords reflects increasing scholarly focus, particularly during and after the COVID-19 pandemic, which amplified both research interest and relevance. Conclusion: This study highlights the growing global research interest in the psychological effects of cyberbullying. It provides valuable insights into key contributors, research focus, and collaboration trends, serving as a foundation for future studies and prevention efforts.